Finite element simulation of mechanical properties of Rosa roxburghii under compression loading. (24th November 2021) - Lang, Yancheng; Xie, Zhiping; Chen, Luqi
Abstract: It is very necessary to understand the mechanical properties of Rosa roxburghii fruit for harvesting, packaging, processing, transportation, storage, and related equipment design and improvement. This research was to determine the mechanical properties of R. roxburghii fruits through compressive experiments and finite element simulations and to verify the accuracy of the finite element model. In order to achieve finite element analysis, an accurate three‐dimensional (3D) geometric model was reconstructed by applying 3D laser technology and point cloud reconstruction algorithm. The elastic modulus and Poisson's ratio of R. roxburghii fruits were determined to be 4.0 MPa and 0.35 through experiments. The finite element simulation results provided valuable numerical data and visualized stress distribution. The simulation results showed that R. roxburghii fruits were damaged under the loads of 156.2 N (vertical) or 148.3 N (horizontal), with a maximum deformation of 5.0 mm (vertical) or 6.93 mm (horizontal), respectively. In the vertical and horizontal compression positions, the maximum relative errors between the experimental results and the finite element model are 24.71 and 13.99%, respectively. The results of the compressive strain energy of the fruit showed that the maximum relative error between the experimentally measured strain energy and the strain energy calculated by FEM simulation was 9.20 and 2.09% in the vertical and horizontal directions, respectively. Practical Applications: As there is no relevant literature on the mechanical analysis of Rosa roxburghii fruit, the finite element method has been successfully applied to analyze the mechanical properties of R. roxburghii fruit under compressive load. At the same time, the simulation results have also been verified by experimental data, and the finite element technology has certain application prospects in food processing engineering. This study proposes a method based on 3D scanning technology and point cloud reconstruction algorithm to reconstruct an accurate geometric model of R. roxburghii fruit for finite element simulation, and conducts an in‐depth analysis on the stress, strain, and strain energy of the fruit. The purpose of this article is to propose a reliable method to predict the mechanical properties of the fruits under compressive load. The finite element simulation results can not only provide the basic data needed for fruit packaging and protection but also can be used for the design of automated fruit picking manipulators and the improvement of fruit processing equipment.